Studi Literatur: Determinan Kunjungan Ibu Balita ke Posyandu Tahun 2021-2025 - Siti Ma’wah Doifah; Luqman Effendi (Lembaga Pengembangan Kinerja Dosen, 2026)
Posyandu (Integrated Health Post) is a community based health center that demonstrates community participation in health development. Posyandu provides a variety of integrated services, including family planning, maternal and child health (MCH), nutrition, immunization, and diarrhea management, all implemented simultaneously. Posyandu is also included in the Community-Based Health Efforts (UKBM) and is part of the Village Public Health Institution's activities. This study aims to analyze factors influencing mothers' visits to Posyandu by toddlers. The research method used was a literature review, examining ten relevant scientific articles. The article search was conducted through Google Scholar and Garuda databases, with the inclusion criteria being Indonesian-language articles published within the last five years (2021–2025). The study results indicate that factors influencing mothers' visits to Posyandu include knowledge, attitudes, education, employment, family support, the role of cadres, and access to health services. These findings emphasize the importance of strengthening the role of cadres and family support in increasing Posyandu visits.